PERAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DALAM PEMELIHARAAN AKSES JALAN MENUJU DESTINASI WISATA KABUPATEN KARIMUN TAHUN 2018 - Umi Latifah; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Karimun Regency is a national strategic area in the form of Indonesia's maritime border area as well as a trade and free port area. This is the background of the importance of efforts to develop regional potential. One of the efforts is to have supporting facilities in the form of maintaining road access to Karimun tourist destinations (pelawan beach tourism and limau stone tourism) to encourage economic growth and tourism for the growth of Karimun Regency. The maintenance of road access in Karimun Regency is under the Ministry of Public Works, which is not immune from the interference of the local government, namely the Public Works and Spatial Planning Office with the aim of encouraging economic growth and tourism for areas as border areas.                     The purpose of this study is to find out how the role of the public works service and spatial planning in maintaining road access to tourist destinations in Karimun Regency (Pelawan Beach and Limau stone Tourism) in 2018. This research uses a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques.                        The results of this study are the implementation of the role of the public works department and spatial planning in maintaining road access to Karimun Regency tourist destinations (Pelawan Beach tourism and limau stone tourism) which is carried out by the Regional Government which has the authority to maintain road access in the Karimun Regency area optimally. Authority is a very important thing in government because one of the main principles that is used as the basis for every governance and state administration in every state law in exercising its authority must be based on applicable laws or legal regulations (legality principle). Various efforts have been made but these are inseparable from inhibiting factors, namely limited budgetary factors, community participation, inadequate facilities and infrastructure as well as the total quality of Human Resources. Keywords: Role, Authority, Road maintenance, Tourist destination.